1995
DOI: 10.1002/gps.930100806
|View full text |Cite
|
Sign up to set email alerts
|

Glucose metabolic rate and progression of illness in Alzheimer's disease

Abstract: Thirty‐eight patients with mild to moderate Alzheimer's disease (AD) underwent a neuropsychological test battery and 18‐fluoro‐2‐deoxyglucose (FDG) positron emission tomography (PET) before beginning and at the end of a randomized double‐blind study of an experimental treatment. Twelve of the patients took placebo. In the placebo patients, Mini‐Mental State (MMS) score decreased and cortical metabolism increased significantly over the 6‐month course of the study. Correlations of metabolism with neuropsychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The subsequent decreased ATP production 27,42 could be shown with 31 P magnetic resonance spectroscopy investigations 52 . Both techniques allow a follow‐up of the progression of the decrease of glucose turnover in patients at risk of developing Alzheimer's disease 58,64 …”
Section: Amyloid Generation: a Results Of Abnormal Beta Amyloid Precurmentioning
confidence: 99%
“…The subsequent decreased ATP production 27,42 could be shown with 31 P magnetic resonance spectroscopy investigations 52 . Both techniques allow a follow‐up of the progression of the decrease of glucose turnover in patients at risk of developing Alzheimer's disease 58,64 …”
Section: Amyloid Generation: a Results Of Abnormal Beta Amyloid Precurmentioning
confidence: 99%
“…Using positron emission tomography (PET) with 18 F-2-deoxyglucose (FDG) as a tracer, Haxby et al (1988) found parietal hypometabolism to correlate with prominent impairment in verbal comprehension, calculation, and visuospatial tasks, whereas frontal hypometabolism was correlated with more impaired verbal fluency and attention. An association between frontal cortical changes and impaired performance in verbal fluency tasks was also reported by Mann et al (1992) and Siegel et al (1995). Although these studies underline the importance of frontal, parietal, and temporal changes in AD, the question of how these heterogeneous cerebral changes contribute to memory impairment remains unresolved.…”
Section: Introductionmentioning
confidence: 85%
“…Although memory problems are often subtle in the earliest stages of AD, their steady progression may leave the patient in an almost entirely amnestic condition. Recent neuroimaging studies have demonstrated structural (Jobst et al 1992;Pantel et al 1997), spectroscopic (Lazeyras et al 1998), and functional (Mann et al 1992;Pearlson et al 1992;Siegel et al 1995; for reviews, see Santens and Petit 1997;Small and Leiter 1998) cerebral changes in AD. These changes strike primarily the temporal and parietal association cortices but generally extend to the frontal cortex with progression of the disease (Buchsbaum et al 1991;Haxby et al 1988;Mann et al 1992;Mielke et al 1994;Smith et al 1992;Stein et al 1998), especially with secondary depression (Hirono et al 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…A considerable body of evidence suggests that a defect in energy metabolism may occur in AD (7,34,47). Positron emission topographic studies of cerebral glucose metabolism have shown that a decrease in the parietal and temporal cortices occurs early in the course of AD and may precede cognitive deficits (21, 34,72). Moreover, the reduction in cerebral glucose metabolism has been shown to correlate significantly with severity of dementia (19.48.76).…”
Section: Effects On Reduced Brain Energy Metabolism In Aged Ratsmentioning
confidence: 99%